Diversidade genética de acessos do banco ativo de germoplasma de mangabeira - Costa, Tatiana Santos (2010)
Due to the great social, economic and cultural context which Mangabeira (Hancornia speciosa) represents, as well as the intense devastation of the areas where it occurs naturally, was implemented in 2006, the Active Bank Mangabeira Embrapa Tabuleiros Costeiros (BAGMangaba) in Itaporanga d'Ajuda, SE. The Genebank (bags) gather genetic constitutions of different backgrounds and represent sources of genes for breeding programs. Therefore, it is essential that the breeder knows the genetic diversity of germplasm available. The aim of this study was to estimate the genetic variability of 55 accessions of BAG Mangaba RAPD markers (Polymorphic DNA Randomly Amplified). 13 primers were used for synthesis (primers), which generated 82 fragments (bands), 72 polymorphic, which were analyzed as binary data. From these data yields a similarity matrix using Jaccard's coefficient. With this coefficient and the UPGMA method agglomerative cluster analysis were performed using the programs FreeTree; TreeView and XLSTAT and a method of resampling (bootstraps) generated dendrograms that used to distinguish among the accessions. The similarity ranged from 0.02 to 0.91. Individuals were more similar CA4 and CA5 and more divergent lining IP6 and PR4. From the SGM were detected at the pair of individuals and CA5 CA4, CA1 and CA2, PT2, and PT3 are considered similar (clones). Through Clustering UPGMA and PCoA was possible to identify five groups. The high level of polymorphism (95%) suggests that RAPD markers are a useful tool to detect genetic differences among accessions of H. speciosa, assisting in a future program to improve the species.